PENGARUH AUDIT QUALITY DAN AUDIT TENURE TERHADAP AUDIT REPORT LAG PERUSAHAAN MANUFAKTUR 2013—2015 - Pandu Maulana B (Parsimonia - Jurnal Ekonomi dan Bisnis, 2018)
This research aims to prove the effect of audit quality and audit tenure on audit report lag. Audit quality can be measured with the public accounting firm size such as Big Four and Non Big Four. Audit tenure measured by the employment contract with the company. Audit report lag measured by the length of audit completion the length of completion of the audit by the date of the last financial year based on the last date of book year to last date of audit report year. The result of this research found out that audit quality did not affect auditor report lag, while audit tenure affected audit report lag. These results are due to audit quality measured by the size of the public accounting firm, have the result of completion of the audit report lag is not much different. Meanwhile, the audit tenure affected audit report lag, because, the longer the employment contract done by the company and public accounting firm, will provide knowledge to the auditor so that the audit can be completed on time.